Penatalaksanaan Fisioterapi Pada Kasus Post Orif (OpenReduction Internal Fixation) Fracture SuprakondilerHumeri Di Rsud Dr. Soehadi Prijonegoro - Fauzi, Nila Astriput, Maskun Pudjianto, SMPH, M.Kes (2017)
Background : The supracondylar humerus fracture is a fracture exactly located in proximal trochlea and capitulum humeri. It is a fracture that is often found on the elbow. In this case, it is done installation method of internal fixation that is K-Wire and it is resulted existences of the problematic of physiotherapy i.e. tenderness, motion pain, decreased muscle strength, limited scope of motion of the joints and decreased functional activity. Physiotherapy can use infra red modalities, active motion exercises, passive motion exercises, isometric contractions and hold relax. Purposes : The methodology which is used in this writing refers to clinical status, such as examination of pain with vas, limited range of motion of joints with goniometer, decreased muscle strength with mmt, functional activity ability with Barthel index. To know the benefits of physiotherapy management with infra red modalities, active motion exercises, passive motion exercises, isometric contractions and hold relax on post-ORIF conditions supracondylar humerus fractures against: pain reduction, increased muscle strength, increased scope of joint motion, increased functional activity. Results: From the physiotherapy action that have been done with infra red modality, active motion exercises, passive motion exercises, isometric contraction and hold relax proved to reduce pain, increase muscle strength, increase the scope of joint motion, have not been able to increase the ability of functional activity.